18.6k views
4 votes
Y+2 = -3(x – 4)

Complete the missing value in the solution to the equation.

(?, -2)

User Drch
by
6.6k points

1 Answer

6 votes

Answer:

The missing value in the solution to

the equation will be:


  • x=4

Explanation:

Given the equation


y+2\:=-3\left(x\:-\:4\right)

As the value of y = -2 is given.

so substituting the value y = -2 in the equation to find the missing value


\left(-2\right)+2\:=-3\left(x\:-\:4\right)

switch the sides


-3\left(x-4\right)=\left(-2\right)+2


\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a


-3\left(x-4\right)=-2+2


-3\left(x-4\right)=0


\mathrm{Divide\:both\:sides\:by\:}-3


(-3\left(x-4\right))/(-3)=(0)/(-3)


x-4=0


x=4

Therefore, the missing value in the solution to

the equation will be:


  • x=4
User Kdmurray
by
6.3k points